2020
DOI: 10.1038/s41598-020-62161-1
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri 5454 and Bifidobacterium animalis ssp. lactis 5764 improve colitis while differentially impacting dendritic cells maturation and antimicrobial responses

Abstract: Crohn’s disease is linked to a decreased diversity in gut microbiota composition as a potential consequence of an impaired anti-microbial response and an altered polarization of T helper cells. Here, we evaluated the immunomodulatory properties of two potential probiotic strains, namely a Bifidobacterium animalis spp. lactis Bl 5764 and a Lactobacillus reuteri Lr 5454 strains. Both strains improved colitis triggered by either 2,4,6-trinitrobenzenesulfonic acid (TNBS) or Citrobacter rodentium infection in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 44 publications
2
62
0
1
Order By: Relevance
“…Bacteria-primed bone marrow derived dendritic cells (BMDCs) were differentiated from the bone marrow of BALB/c mice as described previously [ 60 , 61 ]. On day 9 after differentiation, cells were stimulated by bacteria (PF-BaE5 and PF-BaE11 strains) at a ratio bacteria/cells 10:1 for 5 h (gene expression analysis) or 24 h (flow cytometry analyses of co-stimulatory markers, co-culture with CD4 + T cells).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria-primed bone marrow derived dendritic cells (BMDCs) were differentiated from the bone marrow of BALB/c mice as described previously [ 60 , 61 ]. On day 9 after differentiation, cells were stimulated by bacteria (PF-BaE5 and PF-BaE11 strains) at a ratio bacteria/cells 10:1 for 5 h (gene expression analysis) or 24 h (flow cytometry analyses of co-stimulatory markers, co-culture with CD4 + T cells).…”
Section: Methodsmentioning
confidence: 99%
“…In the report, the difference between colitis models was also visible, nevertheless, it was not a subject of assessment. Another research group headed by Hrdy [ 85 ] proved that probiotic strains affected host cells in many ways. The study was based on the murine model of TNBS-induced colitis, and the mechanism of action of Bifidobacterium animalis spp.…”
Section: Probiotics Treatment and Protection From Ibdmentioning
confidence: 99%
“…Recently, Le and Yang [ 114 ] reported that IBD could be potentially prevented and managed by L. plantarum , in which the modulation of the ratio of T helper cell 1 (Th1) and T helper cell 2 (Th2) plays an important role. In addition to IBD, it has been reported that CD, which was induced by either TNBS or a mucosal pathogen Citrobacter rodentium , could be potentially ameliorated by L. reuteri in a mouse model [ 115 ]. Wang et al [ 110 ] investigated the anti-inflammatory effect of L. plantarum strain ZDY2013 and B. bifidum WBIN03 strains on dextran sodium sulphate (DSS)-induced UC in a mouse model.…”
Section: Potential Applicationmentioning
confidence: 99%